2003
DOI: 10.1114/1.1630600
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Soluble Gas Exchange in the Airways and Alveoli

Abstract: A mathematical model of heat, water and soluble gas exchange in the airways and alveoli was used to predict the location of soluble gas exchange in the lung. A previously published model of heat, water and soluble gas exchange in the airways was improved by incorporating anatomical data on the airway wall to better describe the bronchial circulation and expanding the model to include a time varying description of soluble gas concentration in the alveoli. Next, the model was validated using two experimental dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(166 citation statements)
references
References 40 publications
7
157
0
2
Order By: Relevance
“…It cannot be excluded that HCN is to some extent filtered in the nasal mucosa. In general, since hydrogen cyanide is a hydrophilic species (water air partition coefficient of 320), the gas exchange might take place not only at the alveolar interface but also in the mucosa of the lungs and airways [36]. Hence, one cannot expect a simple correlation between end-tidal breath, alveolar breath and blood HCN levels.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be excluded that HCN is to some extent filtered in the nasal mucosa. In general, since hydrogen cyanide is a hydrophilic species (water air partition coefficient of 320), the gas exchange might take place not only at the alveolar interface but also in the mucosa of the lungs and airways [36]. Hence, one cannot expect a simple correlation between end-tidal breath, alveolar breath and blood HCN levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that EEAC is less than AAC due to the exchange of alcohol in the airways during both inspiration and expiration. 2,3,8 Earlier studies have examined the assumption of equality between end-exhaled and AAC by comparing ABT values with blood measurements and found a considerable amount of variation in the ratio of EEAC to BAC. For further evidence regarding the lack of end-exhaled and alveolar equality, two studies 10,13 have shown that EEAC is approximately 15-20% lower than AAC on average (obtained using isothermal rebreathing).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophilic compounds such as acetone have been demonstrated to interact with the water-like mucus membrane lining the conductive airways, an effect which has become known as wash-in/washout behavior. Extensive details can be found, e.g., in [54,55,7,8].…”
Section: Acetone Backgroundmentioning
confidence: 99%